Value for Money in Mexico? Including the Missing Risks in Infrastructure Project Evaluation - Heald, Jeremy (International Journal of Economics and Financial Issues, 2019)
According to economists and financiers of multilateral organizations, banks and consultancies, ‘Public Private Partnerships’ are the answer to traditional inefficiencies in infrastructure procurement, providing ‘Value for Money’. While that proposition requires corroboration, so does the reliability of the methodology underlying the measurement of it, especially before project implementation with a view to improving current investment decisions, but also after, to appraise impact and improve future infrastructure procurement. Based on a review of the international literature on infrastructure evaluation together with direct experience by the author of Mexican procurement, the article makes specific recommendations for rebalancing the economic measurement of risk and Value for Money. It does so by including missing risks, flexibility and stakeholders in the Value for Money calculation. The proposal is timely considering the erosion of public confidence in the Value for Money methodology and the inclination of stakeholders to avoid appraisal obligations and public scrutiny. Keywords: Public Private Partnerships, Evaluation, Value for Money, Risk, Stakeholders JEL Classifications: O2, 022 DOI: https://doi.org/10.32479/ijefi.8090